A novel gene, optrA, that confers transferable resistance to oxazolidinones and phenicols and its presence in Enterococcus faecalis and Enterococcus faecium of human and animal origin. (14th May 2015) - Wang, Yang; Lv, Yuan; Cai, Jiachang; Schwarz, Stefan; Cui, Lanqing; Hu, Zhidong; Zhang, Rong; Li, Jun; Zhao, Qin; He, Tao; Wang, Dacheng; Wang, Zheng; et al.
Abstract: Objectives: The oxazolidinone-resistant Enterococcus faecalis E349 from a human patient tested negative for the cfr gene and 23S rRNA mutations. Here we report the identification of a novel oxazolidinone resistance gene, optrA, and a first investigation of the extent to which this gene was present in E. faecalis and Enterococcus faecium from humans and food-producing animals. Methods: The resistance gene optrA was identified by whole-plasmid sequencing and subsequent cloning and expression in a susceptible Enterococcus host. Transformation and conjugation assays served to investigate the transferability of optrA . All optrA -positive E. faecalis and E. faecium isolates of human and animal origin were analysed for their MICs and their genotype, as well as the location of optrA . Results: The novel plasmid-borne ABC transporter gene optrA from E. faecalis E349 conferred combined resistance or elevated MICs (when no clinical breakpoints were available) to oxazolidinones (linezolid and tedizolid) and phenicols (chloramphenicol and florfenicol). The corresponding conjugative plasmid pE349, on which optrA was located, had a size of 36 331 bp and also carried the phenicol exporter gene fexA . The optrA gene was functionally expressed in E. faecalis, E. faecium and Staphylococcus aureus . It was detected more frequently in E. faecalis and E. faecium from food-producing animals (20.3% and 5.7%, respectively) than from humans (4.2% and 0.6%, respectively). Conclusions: Enterococci with elevated MICs of linezolid and tedizolid should be tested not only for 23S rRNA mutations and the gene cfr, but also for the novel resistance gene optrA .